"Tan Divina Amazona": The Legend of Isabel the Catholic Queen in Luis Vélez de Guevara's La serrana de la Vera. - Oechler, Christopher C. (Neophilologus, 2020)
In La serrana de la Vera (1613), Luis Vélez de Guevara provides an updated take on the medieval serrana, a lustful and dangerous mountain woman. He sets her legendary actions during the reign of Isabel I of Castile, and the play follows the protagonist Gila's degeneration from an impressively strong labradora to a demonic man-murderer who boasts of over two thousand kills. Critics have noted the strong affinity between Queen Isabel and the serrana Gila and have focused on the play as an exemplum for curbing female behavior that exceeds the norms imposed by a patriarchal society. While the play creates a mirroring effect whereby Gila adopts and emulates Isabel's masculine traits, I maintain that Gila's virile behavior and starry-eyed admiration of Isabel entail more than a warning for women; her portrayal questions and challenges Isabel's legend as presented in writings and remembrances of the queen. At the heart of this play, beyond the ambiguous gender of Gila, is the playwright's challenge to the official mythic construction of royal personas. Vélez de Guevara takes an already legendary serrana character from popular folklore and links her with the queen, emphasizing how Isabel's history approximates and in many instances is indistinguishable from myth. La serrana de la Vera ends as a tragedy, thus emphasizing the untenability of Isabel's dehumanizing legend.